Have integrated landscape approaches reconciled societal and environmental issues in the tropics? - Reed, J.D.; Vianen, J. van; Barlow, J.; Sunderland, Terry C.H. (Elsevier, 2017)
Landscape approaches to integrated land management have recently gained considerable attention in the scientific literature and international fora. The approach is gaining increasing support at governmental and intergovernmental levels, as well as being embraced by a host of international research and development agencies. In an attempt to determine whether, and how, these approaches compare with previous conservation and development paradigms, we reviewed the implementation of integrated landscape approaches across the tropics. Within the scientific literature we fail to find a single applied example of the landscape approach in the tropics that adequately—that is with reliable, in depth collection and reporting of data—demonstrated the effective balancing of social and environmental trade-offs through multi-scale processes of negotiation for enhanced outcomes. However, we provide an assessment of 150 case studies from unpublished grey literature and 24 peer-reviewed studies that exhibit basic characteristics of landscape approaches. Our findings indicate that landscape approaches show potential as a framework to reconcile conservation and development and improve social capital, enhance community income and employment opportunities as well as reduce land degradation and conserve natural resources. However, comprehensive data on the social and environmental effects of these benefits remain elusive. We identify key contributing factors towards implementation, and progress, of landscape approaches and our findings suggest that multi-level, or polycentric, governance structures relate well with intervention success. We conclude that landscape approaches are a welcome departure from previous unsuccessful attempts at reconciling conservation and development in the tropics but, despite claims to the contrary, remain nascent in both their conceptualization and implementation.